A length-dependent evolutionarily conserved pathway controls nuclear export of circular RNAs - Huang, Chuan (Genes Dev, 2018)
Circular RNAs (circRNAs) are generated from many protein-coding genes. Most accumulate in the cytoplasm, but how circRNA localization or nuclear export is controlled remains unclear. Using RNAi screening, we found that depletion of the Drosophila DExH/D-box helicase Hel25E results in nuclear accumulation of long (>800-nucleotide), but not short, circRNAs. The human homologs of Hel25E similarly regulate circRNA localization, as depletion of UAP56 (DDX39B) or URH49 (DDX39A) causes long and short circRNAs, respectively, to become enriched in the nucleus. These data suggest that the lengths of mature circRNAs are measured to dictate the mode of nuclear export.